Evaluation of in vitro growth-inhibitory effect of carvacrol and thymol combination against Staphylococcus aureus in liquid and vapour phase using new broth volatilization chequerboard method - Netopilova, Marie; Houdkova, Marketa; Rondevaldova, Johana; Kmet, Vladimir; Kokoska, Ladislav (Fitoterapia, 2018)
Carvacrol and thymol, both plant-derived volatile compounds, have extensively been studied individually as well as in combination with other agents for their antimicrobial activity in liquid phase. However, in contrast to well-established assays for testing of antimicrobial combinatory effects in liquid media, there are no standardized methods for evaluation of interactions between volatile compounds in vapour phase. The objective of this study was to verify new broth volatilization chequerboard method by testing the combination of carvacrol and thymol and to determine in vitro inhibitory effect of these compounds in liquid and vapour phase against twelve Staphylococcus aureus strains. The new method, based on combination of standard microdilution chequerboard and new broth volatilization tests allowing calculation of fractional inhibitory concentrations (FICs), was used. Combination of carvacrol and thymol produced the additive antimicrobial effect against all strains tested. In several cases, they reached ΣFIC values lower than 0.6, which can be considered as a strong additive interaction. The best result was found in vapour phase against one standard strain at combination of 128 μg/mL of carvacrol and 16-256 μg/mL of thymol (ΣFIC = 0.51) and in liquid phase against one clinical isolate at combination of 256 μg/mL of carvacrol and 256 μg/mL of thymol (ΣFIC = 0.53). The study verified that the new technique is suitable for simple and rapid high-throughput combinatory antimicrobial screening of volatile compounds simultaneously in vapour and liquid phase and that it allows determination and comparison of MIC and FIC values in both, liquid and solid media.
Keywords: monoterpeny; Volatilization; Vapour phase; Combinatory antimicrobial effect; rychlé screeningové testy; High-Throughput Screening Assays; Volatile compound; cymeny; volatilizace; mikrobiální testy citlivosti; Cymenes; thymol; Microbial Sensitivity Tests; Monoterpenes; Essential oil; Thymol; Staphylococcus aureus; Fractional inhibitory concentration